ANALISIS PRESISI MENGUNAKAN METODE ALTMAN DAN ZMIJEWSKI UNTUK MEMPREDIKSI TERJADINYA FINANCIAL DISTRESS - Sukma, Melati; Suherman, Acep (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to determine the accuracy of the bankruptcy method or financial difficulties using the Altman method, zmijewski. The variables used in this study are the Altman and zmijewski methods. This research was conducted using a qualitative method with a comparative approach. The population in this study is the financial statements of the 2016-2018 Cement sub-sector of cement companies and 36 financial statements are sampled. In this study sampling with saturated sampling technique. Data collection techniques are literature study and observation. The data analysis technique used is the data process. The results of this study indicate: the independent variable is the altman method, zmijewski while the dependent variable is financial distress. The results of this study indicate that the more precise method is the Zmijewski method